On the identity of the subject in the institutionalisation of scientific theories - Orozco Echeverri, Sergio H. (Estudios de Filosofía, 2014)
The social studies of science and in particular the sociology of scientific knowledge (SSK), have criticized the philosophies of science because they are based on epistemologies centered on the individual as a subject of knowledge, at the expense of an analysis that accounts for scientific communities, an explanation of scientific knowledge focused on the individual is unable to account for the traditions and current state of science. This article argues, however, that SSK does not dilute the subject in the scientific community but, on the contrary, allows us to define it in their interaction with others, the interpretation and organization of knowledge of nature. This is done using the notion of identity of the subject as a practitioner of science.